Attrition at the final donor stage among unrelated haematopoietic stem cell donors: the British Bone Marrow Registry experience. Issue 5 (17th June 2019) - Balassa, K.; Griffiths, A.; Winstone, D.; Li, Y.; Rocha, V.; Pawson, R.
SUMMARY: Objectives: To investigate attrition at the finally selected donor stage among British Bone Marrow Registry (BBMR) donors, all recruited from blood donors. Background: The success of searches for unrelated stem cell donors relies on the existence of large international donor registries and the availability of registered donors when matched with a patient. Withdrawal of donors may adversely affect patient outcomes. Materials/Methods: Data on 2942 planned donations were analysed to assess donor‐related deferral rates and associated factors. Results: Overall, 20·2% of requests were cancelled. Transplant centres activated more than half of the cancellations (52·6%). Donor reasons accounted for 46·7% of cancellations (9·4% of requests), of which 61·7% happened for medical and 38·3% for personal reasons. Medical ineligibility of the donor was associated with increasing age (odds ratio [OR] = 1·36, P  = 0·011) and peripheral blood stem cell source (OR = 2·22, P  = 0·006), and there was some evidence of association with low blood donation reliability (OR = 1·52, P  = 0·054). The blood donor reliability score relates to blood donation, and the score worsens if donors consistently fail to attend a donation session when invited. Withdrawal on personal grounds showed associations with donor age (OR = 1·72, P  = 0·017, 30–40 years vs other ages), peripheral blood stem cell source (OR = 2·43, P  = 0·010) and low blood donor reliability (OR = 1·94, P  = 0·007). Conclusions: To our knowledge, this is the first report on all‐cause cancellation at the finally‐selected donor stage for international stem cell donor provision, showing 9·4% donor‐related cancellation rate. Scores associated with blood donation reliability may be useful to predict stem cell donor withdrawal.